The survey of mindfulness in multiple sclerosis patients and its association with attachment style - Mohamadirizi, Soheila (J Educ Health Promot, 2017)
BACKGROUND: Mindfulness may be conceptualized as a dispositional trait which differs across individuals, so this study was, therefore, designed to determine the survey of mindfulness in multiple sclerosis (MS) patients and its association with attachment style. MATERIALS AND METHODS: This was a cross-sectional study which was conducted in Kashani Hospital affiliated to Isfahan University of Medical Sciences, Iran, in 2013. Samples were 210 adult patients who suffered from MS completed demographic and disease characteristics questionnaire, Five Factor Mindfulness Questionnaire and adult attachment style. The SPSS version 16 software was used to conduct statistical tests including t-test, NOVA, and Pearson correlation. RESULTS: The means of age and duration of illness were (33/96 ± 9/5) years and (24/3 ± 6/3) month, respectively. Most patients were married (66/1%), without university education (62/8%) and with incomes suffice (63%). The majority of the patients had received beta-interferon (55/4%) as their main treatment. The mean ± standard deviation attachment style and mindfulness were 25/6 ± 11/6 and 79/8 ± 25/6, respectively. Furthermore, there was a significant negative correlation between the attachment style score and mindfulness score (P = 0.001, r = −0.32). CONCLUSION: The result shows that stronger association between mindfulness and attachment can reflect the beneficial effects of mindfulness interventions on both mindfulness and attachment and it can provide some evidence that mindfulness interventions may enhance secure attachment.